2005
DOI: 10.1111/j.1472-765x.2004.01633.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Saccharomyces cerevisiae on the stability of the herbicide glyphosate during bread leavening

Abstract: Aims: To investigate the ability of baker's yeast (Saccharomyces cerevisiae) to degrade the herbicide glyphosate during the fermentation cycle of the breadmaking process. Methods and Results: Aqueous glyphosate was added to bread ingredients and kneaded by commercially available breadmaking equipment into dough cultures. Cultures were incubated in the breadmaker throughout the fermentation cycle. The recovery of glyphosate levels following fermentation was determined, thus allowing an estimation of glyphosate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 15 publications
4
16
0
1
Order By: Relevance
“…The finding that the herbicide S, differently from its pure AI G, had clear negative effects on K310 was in accordance with findings by Low and colleagues. They reported that bakers' yeast can metabolize up to 20% of G during the bread making process, probably with detoxification mechanisms which can result in the production of new degradation compounds, whose action is still unknown (Low et al, 2005). Additionally, our finding is also in good agreement with a consistent number of reports indicating that commercial formulations containing G are much more toxic than G alone in several organisms/cells (dos Tsui & Chu, 2003;Peixoto, 2005;Benedetti et al, 2004).…”
Section: Yeast Colony Forming Ability and Fermentative Performancesupporting
confidence: 81%
“…The finding that the herbicide S, differently from its pure AI G, had clear negative effects on K310 was in accordance with findings by Low and colleagues. They reported that bakers' yeast can metabolize up to 20% of G during the bread making process, probably with detoxification mechanisms which can result in the production of new degradation compounds, whose action is still unknown (Low et al, 2005). Additionally, our finding is also in good agreement with a consistent number of reports indicating that commercial formulations containing G are much more toxic than G alone in several organisms/cells (dos Tsui & Chu, 2003;Peixoto, 2005;Benedetti et al, 2004).…”
Section: Yeast Colony Forming Ability and Fermentative Performancesupporting
confidence: 81%
“…Contrary to data reported by Low et al . (), our results also suggest that dough fermentation would not be an effective technique to degrade glyphosate residues in wheat.…”
Section: Discussionmentioning
confidence: 98%
“…According to Low et al . (), yeast would metabolise about 20% of pure glyphosate in dough fermented for only 1 h. To our knowledge, no scientific evidence has been reported on the effect of commercial glyphosate preparation on baker's yeast fermentative activity. Little information is also available on the impact of yeast fermentation and bread baking on the degradation of glyphosate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the presence of four fungicide residues (cyprodinil, fludioxinil, glyphosate, and pyrimethanil) during fermentation affected the aromatic composition of Vitis vinifera white wines inoculated with S. cerevisiae strains, causing a decrease in organoleptic quality [12][13][14]. Also, analysis of the S. cerevisiae gene expression pattern in response to lindane (an organochlorine pesticide) revealed mitochondrial dysfunction, oxidative stress, and ionic homeostasis [15,16].…”
Section: Introductionmentioning
confidence: 99%